OVERLAPPING BETWEEN PROVINCIAL REGIONAL REGULATIONS WITH REGENCY/MUNICIPAL LOCAL REGULATIONS ON THE REGULATED MATERIAL VIEWED FROM THE LAW NUMBER 12 OF 2011 REGARDING ESTABLISHMENT OF LEGISLATION - Iip Septian; Amancik Amancik; Patricia Ekowati Suryaningsih (Universitas Bengkulu, 2020)
The occurrence of overlapping between provincial regional regulations and regency/municipal regulations on the same material may create legal problems, because if they are not properly regulated, then authority in the implementation and enforcement of overlapping regional regulations becomes biased, this condition resulted in the failure to fulfill the justice and legal certainty aspects, as well as the benefit aspect, because there are dual regulatory arrangements, which are the regency/municipality regulations and the provincial regulations, in which hierarchically the two regional regulatory instruments are unequal, where the provincial regulation has a higher position than regency/municipal regulations. The similarity of content material between provincial and regency/municipal regulations as referred to in the provisions of Article 14 of Law Number 12 Year 2011 concerning the Establishment of Legislation makes it possible to regulate the same material between provincial and regency/municipal regulations. In the context of provincial and regency/municipal regulations governing the same material, then orders, restrictions, permits and licenses must be clear and resolute, where the regency/municipal regulations cannot contain different orders, prohibitions, licenses and permits which has been formulated in the provisions of the provincial regulation, or in other words, the norm formulation in regency/municipal regulations shall not be contradictory to the norms regulated in provincial regulations. Essentially, regency/municipal regulations can only regulate matters that have not been regulated in the above legislation.